The genus Sicoderus Vanin 1986 (Coleoptera: Curculionidae: Curculioninae: Erodiscini) in the West Indies - Anderson, Robert S. (Zootaxa, 2018)
The genus Sicoderus Vanin is revised for the West Indies. A total of 32 species are known with 18 new species described herein as follows: Sicoderus aeneus (Haiti), S. alternatus (Dominican Republic), S. bautistai (Dominican Republic, Haiti), S. beatyi (Cuba), S. bipunctiventris (Cuba), S. caladeler (Cuba), S. detonnancouri (Dominican Republic), S. franzi (Puerto Rico), S. guanyangi (Dominican Republic), S. humeralis (Dominican Republic), S. lucidus (Dominica), S. medranae (Dominican Republic, Haiti), S. perezi (Dominican Republic), S. pseudostriatolateralis (Dominican Republic, Haiti), S. striatolateralis (Dominican Republic), S. thomasi (Haiti), S. turnbowi (Dominican Republic), and S. woodruffi (Grenada). All species are described or redescribed, natural history information is summarized and a listing of locality data from all specimens examined is included. A key is provided to all West Indian species of the genus. All species distributions are mapped and all (excepting S. propinquus Vanin) are represented by habitus images and images of male genitalia.